The Need for Palliative Care Education and Training in Liberia and Indonesia: A Literature Review - Stephens, Moses Tende; Rochmawati, Erna (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Palliative care education is still in its infancy in some countries, including Liberia and Indonesia. The palliative care education resources for health care professionals in Liberia and Indonesia have not been emerging into the tutorial curriculum for advancement. The purpose of this review was to identify the availability of palliative care education and factors that influences palliative care education in Liberia and Indonesia. In this study, the researcher performed a literature review of articles found in Scopus, PubMed, Google Scholar, and Science Direct, published until December 2021. And then, the eligible studies investigating the need for palliative care education and training in Liberia and Indonesia were included in the study. The quality of the studies was assessed using a critical appraisal tool from the Joanna Briggs Institute, and PRISMA was used to analyze the finding data. And for the results after a comprehensive review, this review included fourteen eligible papers. After intensive study, the paper concluded that three unique common factors affect palliative care education in developing countries. Those factors included poor infrastructure, lack of governmental support, and the unavailability of a palliative care curriculum. Likewise, those articles show the slow development of PC education in Liberia. This literature review shows the lack of palliative care education in Liberia and Indonesia. As identified, there is a gap in palliative care education and training that needs to be answered. Therefore, there is a need to invest in human resources and palliative care education resources because of its slow Improvement.  Pendidikan perawatan paliatif masih dalam tahap awal di beberapa negara, termasuk Liberia dan Indonesia. Sumber daya pendidikan perawatan paliatif untuk profesional perawatan kesehatan di Liberia dan Indonesia belum muncul ke dalam kurikulum tutorial untuk kemajuan. Tujuan dari tinjauan ini adalah untuk mengidentifikasi ketersediaan pendidikan perawatan paliatif dan faktor-faktor yang mempengaruhi pendidikan perawatan paliatif di Liberia dan Indonesia. Dalam studi ini, peneliti melakukan tinjauan literatur artikel yang ditemukan di Scopus, PubMed, Google Scholar, dan Science Direct, yang diterbitkan hingga Desember 2021. Kemudian, studi yang memenuhi syarat yang menyelidiki perlunya pendidikan dan pelatihan perawatan paliatif di Liberia dan Indonesia adalah termasuk dalam studi. Kualitas studi dinilai menggunakan alat penilaian kritis dari Joanna Briggs Institute, dan PRISMA digunakan untuk menganalisis data temuan. Dan untuk hasil setelah tinjauan komprehensif, tinjauan ini mencakup empat belas makalah yang memenuhi syarat. Setelah studi intensif, makalah menyimpulkan bahwa tiga faktor umum yang unik mempengaruhi pendidikan perawatan paliatif di negara berkembang. Faktor-faktor tersebut termasuk infrastruktur yang buruk, kurangnya dukungan pemerintah, dan tidak tersedianya kurikulum perawatan paliatif. Demikian juga, artikel-artikel tersebut menunjukkan lambatnya perkembangan pendidikan PC di Liberia. Tinjauan pustaka ini menunjukkan kurangnya pendidikan perawatan paliatif di Liberia dan Indonesia. Seperti yang teridentifikasi, ada kesenjangan dalam pendidikan dan pelatihan perawatan paliatif yang perlu dijawab. Oleh karena itu, ada kebutuhan untuk berinvestasi dalam sumber daya manusia dan sumber daya pendidikan perawatan paliatif karena Peningkatannya yang lambat.